Sildenafil (Viagra®) prevents and restores LPS-induced inflammation in astrocytes - de Santana Nunes, Ana Karolina; Rapôso, Catarina [UNESP]; Björklund, Ulrika; da Cruz-Höfling, Maria Alice; Peixoto, Christina Alves; Hansson, Elisabeth (Elsevier, 2016)
Astrocytes are effectively involved in the pathophysiological processes in the central nervous system (CNS) and may contribute to or protect against development of inflammatory and degenerative diseases. Sildenafil is a potent and selective phosphodiesterase-5 (PDE-5) inhibitor, which induces cyclic GMP accumulation. However, the mechanisms of actions on glial cells are not clear. The aim of the present work is to evaluate the role of sildenafil in lipopolysaccharide (LPS)-stimulated astrocytes. The cytoskeleton integrity and Ca2+ waves were assessed as indicators of inflammatory state. Two main groups were done: (A) one prevention and (B) one restoration. Each of these groups: A1: control; A2: LPS for 24 h; A3: sildenafil 1 or 10 μM for 4 h and then sildenafil 1 or 10 μM + LPS for 24 h. B1: control; B2: LPS for 24 h; B3: LPS for 24 h and then LPS + sildenafil 1 or 10 μM for 24 h. Cytoskeleton integrity was analyzed through GFAP immunolabeling and actin labeling with an Alexa 488-conjugated phalloidin probe. Calcium responses were assessed through a Ca2+-sensitive fluorophore Fura-2/AM. The results show that both preventive and restorative treatments with sildenafil (in both concentrations) reduced the Ca2+ responses in intensity and induced a more organized actin fiber pattern, compared to LPS treated cells. This work demonstrated for the first time that astrocytes are a key part of the sildenafil protective effects in the CNS.
Keywords: Calcium; Cytoskeleton; Lipopolysaccharide; Neuroinflammation; Phosphodiesterase-5 inhibitor; Sildenafil